Double Diffusion Encoding for Probing Radiation‐Induced Microstructural Changes in a Tumor Model: A Proof‐of‐Concept Study With Comparison to the Apparent Diffusion Coefficient and Histology. Issue 3 (8th March 2020) - Duchêne, Gaëtan; Abarca‐Quinones, Jorge; Feza‐Bingi, Natacha; Leclercq, Isabelle; Duprez, Thierry; Peeters, Frank
Abstract : Background: Microstructure analyses are gaining interest in cancer MRI as an alternative to the conventional apparent diffusion coefficient (ADC), of which the determinants remain unclear. Purpose: To assess the sensitivity of parameters calculated from a double diffusion encoding (DDE) sequence to changes in a tumor's microstructure early after radiotherapy and to compare them with ADC and histology. Study Type: Cohort study on experimental tumors. Animal Model: Sixteen WAG/Rij rats grafted with one rhabdomyosarcoma fragment in each thigh. Thirty‐one were imaged at days 1 and 4, of which 17 tumors received a 20 Gy radiation dose after the first imagery. Field Strength/Sequence: 3T. Diffusion‐weighted imaging, DDE with flow compensated, and noncompensated measurements. Assessments: 1) To compare, after irradiation, DDE‐derived parameters (intracellular fraction, cell size, and cell density) to their histological counterparts (fraction of stained area, minimal Feret diameter, and nuclei count, respectively). 2) To compare percentage changes in DDE‐derived parameters and ADC. 3) To evaluate the evolution of DDE‐derived parameters describing perfusion. Statistical Tests: Wilcoxon rank sum test. Results: 1) Intracellular fraction, cell size, and cell density were respectively lower (−24%, P  < 0.001), higher (+7.5%, P  < 0.001) and lower (−38%, P  < 0.001) in treated tumors as compared to controls. Fraction of stained area, minimal Feret diameter, and nuclei count were respectively lower (−20%, P  < 0.001), higher (+28%, P  < 0.001), and lower (−34%, P  < 0.001) in treated tumors. 2) The magnitude of ADC's percentage change due to irradiation (16.4%) was superior to the one of cell size (8.4%, P  < 0.01) but inferior to those of intracellular fraction (35.5%, P  < 0.001) and cell density (42%, P  < 0.001). 3) After treatment, the magnitude of the vascular fraction's decrease was higher than the increase of flow velocity (33.3%, vs. 13.3%, P  < 0.001). Data Conclusion: The DDE sequence allows quantitatively monitoring the effects of radiotherapy on a tumor's microstructure, whereas ADC only reveals global changes. Evidence Level: 2. Technical Efficacy: Stage 4. J. Magn. Reson. Imaging 2020;52:941–951.